The Qur’an, Woman and Nationalism In Indonesia: Ulama Perempuan’s Moral Movement - Kusmana Kusmana (Al-Jami'ah Research Centre, 2019)
This paper discusses how 'ulama perempuan' (Female Muslim woman clerics) use religious sources particularly, Qur’an, in their expression of moral movement as seen in media. It also contends that they try to make identity and sense of belonging by inviting themselves and others to participate in improving the wellbeing and cohesion of Indonesia as the nation. Using a descriptiveanalytic method, the study questions about the factors that have made it possible for some Indonesian ulama perempuan to propose a different view, and what do their movement represent in terms of nationalism? In answering them, the study relies its data on their recommendations both at KUPI (Kongres Ulama Perempuan Indonesia), April 25-27, 2017, Cirebon, West Java, and press release presented at Istiqlal Mosque, Jakarta on March 1, 2018, as well as two other recommendations that follow. The study finds that 'ulama perempuan' have made an alternative voice using some of religious sources (the Qur’an) and secular ones through their moral movements in improving the status and role of women, the well beings of children, and environment sustainability. Their movement attracts other agents particularly that of media to magnify the voice and make the movement gear as strong alternative message of soft nationalism.[Artikel ini membahas tentang bagaimana ulama perempuan di Indonesia menggunakan sumber hukum, khususnya al Qur’an dalam aktifitas gerakan moral yang terlihat dalam media massa. Mereka juga mencoba menunjukkan identitas dan perasaan kepedulian dengan melibatkan diri dalam perbaikan keadaan dan kesatuan bangsa. Dengan menggunakan pendekatan deskriptif analitis, tulisan ini mencoba menjawab pertanyaan mengenai factor-faktor yang membuat gerakan mereka memungkinkan untuk mengajukan pandangan alternatif dan merepresentasikan diri dalam wacana nasionalisme. Untuk menjelaskan hal tersebut, studi ini mendasarkan pada hasil rekomendasi mereka pada Kongres Ulama Perempuan Indonesia (KUPI) pertama di Cirebon tahun 2017 dan press release mereka di Masjid Istiqlal pada tanggal 1 Maret 2018, termasuk dua rekomendasi lain berikutnya. Artikel ini memberikan kesimpulan bahwa ulama perempuan mampu membuat pandangan alternatif dengan menggunakan sumber hukum Islam (al Qur’an) dan sumber lain melalui gerakan moral dalam mengangkat status dan peran perempuan, kesejahteraan anak-anak dan isu lingkungan yang berkelanjutan. Gerakan mereka juga menarik perhatian media untuk menguatkan pendapat dan gerakan mereka sebagai pesan alternatif dalam nasionalisme moderat.]